2006
DOI: 10.1177/039463200601900211
|View full text |Cite
|
Sign up to set email alerts
|

Conformation Dependent Pro-Apoptotic Activity of the Recombinant Human Prion Protein Fragment 90-231

Abstract: The transition of prion protein from a mainly a-structured isoform (PrPC) to a~sheet-containing protein (PrPSC) represents a major pathogenetic mechanism in prion diseases. To study the role of PrP structural conformation in prion-dependent neurodegeneration, we analysed the neurotoxicity of PrP in a and~conformations, using a recombinant protein encompassing amino acids 90-231 of the human PrP (hPrP90-231). Using controlled thermal denaturation (53°C, Ih) we converted hPrP90-231 in a structural isoform displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 46 publications
10
46
0
Order By: Relevance
“…SH-SY5Y (Pahlman et al 1995) human neuroblastoma cell line due, to the neuroectodermal origin, is widely used to study intracellular events linked to neurotoxic insults such as trophic factors withdrawal, oxidative stress, DNA damage, and neurodegenerative disorders Corsaro et al 2003). PrP-derived peptides, including hPrP90-231, are able to induce SH-SY5Y cell death through the activation of pro-apoptotic cascades (O'Donovan et al 2001;Thellung et al 2002;Bate et al 2004;Corsaro et al 2006;Chiovitti et al 2007). To develop more effective anti-prion pharmacological approaches, a wide number of molecules have been screened for their ability to counteract biochemical and biological properties of PrP Sc (Trevitt and Collinge 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SH-SY5Y (Pahlman et al 1995) human neuroblastoma cell line due, to the neuroectodermal origin, is widely used to study intracellular events linked to neurotoxic insults such as trophic factors withdrawal, oxidative stress, DNA damage, and neurodegenerative disorders Corsaro et al 2003). PrP-derived peptides, including hPrP90-231, are able to induce SH-SY5Y cell death through the activation of pro-apoptotic cascades (O'Donovan et al 2001;Thellung et al 2002;Bate et al 2004;Corsaro et al 2006;Chiovitti et al 2007). To develop more effective anti-prion pharmacological approaches, a wide number of molecules have been screened for their ability to counteract biochemical and biological properties of PrP Sc (Trevitt and Collinge 2006).…”
Section: Discussionmentioning
confidence: 99%
“…SB203580 abolished hPrP90-231 toxicity but was ineffective on minocycline activity Corsaro et al 2006). On the other hand, minocycline was reported to exert neuroprotection by inhibiting caspase 3 and p38 MAP kinase activity (Chen et al 2000;Guo and Bhat 2007).…”
Section: Hprp90-231 Inhibits Neurotrophic Factor-dependent Erk1/2 Phomentioning
confidence: 99%
“…PrP90-231 sequence corresponds to the protease insensitive core of the pathological prion protein after the cleavage of a large amino-terminal portion (Chen et al, 1995;Parchi et al, 1997). Most importantly, the percentage of b-sheet regions of the recombinant peptide backbone can be increased by high temperature, low pH, high pressure, or reducing agents (Baskakov et al, 2002;Corsaro et al, 2006;Post et al, 2000;Swietnicki et al, 1997;Torrent et al, 2004). This structural shift of PrP90-231 resembles the pathogenic structural refolding of cellular prion protein (PrP C ) into PrP Sc , supporting the relevance of this peptide as a model to study many biochemical and biological aspects of TSE pathogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Without this influx of NK cells, tissues from CCR5-defi-cient (CCR5 -) mice were less able to generate an inflammatory response, had decreased chemokine and interferon-γ production, and a higher parasite burden. Adoptive transfer of CCR5 + / + NK cells into CCR5 -/ -mice restored their ability to survive lethal T. gondii infection, and demonstrated that CCR5 is required for NK cell homing into infected liver and spleen (35)(36)(37)(38). Recently, we found that BALB/c mice infected with E. granulosus respond by producing serum MCP-1 as early as 10 days post infection and we determined the serum MCP-1 and MIP-2 levels as indicators for the inflammatory process (39)(40)(41)(42).…”
Section: Nk Cells and Parasitesmentioning
confidence: 99%
“…In parasites like T. gondii -an intracellular protozoon -Khan and others (35)(36)(37)(38) analyzed the host response of mice deficient in the chemokine receptor CCR5 following infection with the parasite. They found that CCR5 controls recruitment of NK cells into infected tissue.…”
Section: Nk Cells and Parasitesmentioning
confidence: 99%